Economic performance associated with digitalization in Canada over the past two decades - Huju Liu (Economic and Social Reports)
While Canada has embraced digital technologies rapidly and broadly over the past two decades, there is no doubt that the adoption of digital technologies has been amplified and accelerated as a result of the COVID-19 crisis. This article compares the economic performance of sectors where digital inputs have been used more intensively in the production process (digitally-intensive sectors) to that of remaining sectors (non digitally-intensive sectors).